Research gaps and new insights in the evolution of Drosophila seminal fluid proteins - Hurtado, Juan (2021)
While the striking effects of seminal fluid proteins (SFPs) on females are fairly conserved among Diptera, most SFPs lack detectable homologues among the SFP repertoires of phylogenetically distant species. How such a rapidly changing proteome conserves functions across taxa is a fascinating question. However, this and other pivotal aspects of SFPs' evolution remain elusive because discoveries on these proteins have been mainly restricted to the model Drosophila melanogaster. Here, we provide an overview of the current knowledge on the inter-specific divergence of the SFP repertoire in Drosophila and compile the increasing amount of relevant genomic information from multiple species. Capitalizing on the accumulated knowledge in D. melanogaster, we present novel sets of high-confidence SFP candidates and transcription factors presumptively involved in regulating the expression of SFPs. We also address open questions by performing comparative genomic analyses that failed to support the existence of many conserved SFPs shared by most dipterans and indicated that gene co-option is the most frequent mechanism accounting for the origin of Drosophila SFP-coding genes. We hope our update establishes a starting point to integrate further data and thus widen the understanding of the intricate evolution of these proteins.